PERIODONTAL CONDITION OF NEUROCRITICAL PATIENTS ADMITTED TO AN INTENSIVE CARE UNIT IN THE CITY OF RECIFE, PERNAMBUCO STATE, BRAZIL - de Melo, Amanda Carolini Marques; do Nascimento, Zilma Ribeiro; Correia, Maria da Conceição de Barros; dos Santos, Leonardo Cavalcanti Bezerra; Souza, Gustavo Henrique Albuquerque; Souza, Marianna Lorena da Costa; de Lima, Niedje Siqueira; Fontes, Luciana de Barros Correia (Seven Editora, 2025)
Adult neurological patients represent a complex challenge for health care, especially when in critical situations. These are generally more debilitated and dependent, under adverse effects of continued medications and with essential functions related to cognition, communication and identity compromised; a fact that increases the difficulties for personal hygiene, for food and for collaboration in the use of medications, among others. This leads to an increase in debilitating conditions for the body, with negative impacts on the quality of life of them and their network of caregivers. The general objective of this study was to evaluate the periodontal condition of neurocritical adult patients. A cross-sectional, retrospective study was carried out, with the descriptive analysis of secondary data obtained from the medical records of patients admitted to the Neurological ICU of a Reference Hospital, in the city of Recife, during the years 2022 and 2023. Considering 87 patients over 18 years of age who were hospitalized in the ICU in question, most were male (66.7%), with a mean age of 40± 3.7 years, with a length of stay in the ICU of up to three days (56.3%). Some variables proposed in this investigation could not be surveyed, due to the lack of information in the dental history record adopted by the health establishment in question. Patients admitted to the neurological ICU receive oral hygiene with brushes and toothpaste, using 2.0% chlorhexidine gel, twice a day, when intubated. Regarding periodontal conditions, all had some type of periodontal disease. These, in descending order: periodontitis, with the presence of calculus or gingival tartar (49.4%), dental abscess, with suppuration (40.2%) and gingival bleeding (40.2%), tooth mobility (36.8) and biofilm (26.4%). Local dental procedures were related to scaling, drainage of abscesses and tooth extractions, when recommended, due to a risk situation. DOI: https://doi.org/10.56238/sevened2025.018-002